J Surg 2019
DOI: 10.29011/2575-9760.001195
|View full text |Cite
|
Sign up to set email alerts
|

Dysplasia of Cystic Duct and Positive Resection Margins after Cholecystectomy: A Challenging Decision Making Process

Abstract: After cholecystectomy, the presence of dysplasia at resection margins on the cystic duct is rare and evidences lack. A 44-year-old woman underwent a cholecystectomy and a low-grade dysplasia of the cystic duct with involvement of the resection margin was found. A robot-assisted resection of the cystic duct stump was performed as close as possible to the common bile duct and the patient had an uneventful recovery. The histological examination did not show dysplasia on the proximal resection margin. In our exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Finally, three studies were found eligible and considered in this systematic review. [10][11][12] The characteristics of the included studies are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, three studies were found eligible and considered in this systematic review. [10][11][12] The characteristics of the included studies are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…11 More recently, Cianfarani et al reported a case of positive resection margins for lowgrade dysplasia on the cystic duct that was successfully surgical treated with a cystic stump resection. 12 The lack of literature about the surveillance of cystic duct dysplasia makes difficult to draw conclusions. A possible management algorithm is shown in Figure 2.…”
Section: Figure 3: Histologic Exam Showing a Low-grade Dysplasia On Tmentioning
confidence: 99%
“…Nine studies were excluded because did not match inclusion and exclusion criteria. Finally, three studies were found eligible and considered in this systematic review [10][11][12] (Figure 1). The characteristics of the included studies are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of the most recent case report pursued a cystic duct stump excision in light of prior findings of malignancy associated with high-grade cystic duct dysplasia. They however did not offer surveillance after excision [ 16 ]. Similarly, we pursued a laparoscopic cystic duct stump excision, without offering further surveillance or malignancy workup due to normal labs and the patient's excellent postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%